Estimating case duration among common surgeries in the elective operating theater of the Philippine General Hospital for fiscal year 2017-2019 - Sumpay, Andrew B.
Background of the Study: Overestimating surgical case duration or giving more time to a specific surgeon than necessary results to fewer cases. Underestimating of surgical case duration, on the other hand results to nurses and other OR personnel working overtime. In addition, it will also lead to cancellation of cases. Over estimating and under estimating case duration result to low utilization of resources. The operating room is one of the most important areas of the hospital. It is a major contributor to the provision of patient service and is vital to its financial health. Considering all the resources needed to operate, revenue that will generate and numbers of patients that can be operated, improving utilization of resources is important.